446 Utility of Intraoperative Motor-Evoked Potential in L4-5 Lateral Lumbar Interbody Fusion: 3-Year Prospective Study. (1st March 2022) - Alan, Nima; Adams, Gregory; Agarwal, Nitin; Hamilton, David; Miele, Vincent J.; Okonkwo, David O.; Kanter, Adam S.
Abstract : INTRODUCTION: Nerve injury has been reported as high as 23% in direct transpsoas lateral interbody fusion (LLIF), particularly at L4-5. METHODS: This is a prospective, observational, cohort study of consecutive patients who underwent L4-5 LLIF in a 3-year interval from 2018 to 2020. Spontaneous and triggered EMG, somatosensory evoked potentials (SSEP) were routinely recorded. In addition MEPs from quadriceps and anterior tibialis muscle groups were also recorded bilaterally. Transcranial MEP were recorded every 5 minutes from the time of incision. A decrease in amplitude of 50% or more from baseline was considered a positive result, and the surgeon was alerted accordingly. Patient's neurological exam and health related quality of life measures were collected preoperatively, immediately postoperatively, and at the time of follow up at 6 weeks, 3 months, 6 months, 1 and 2 years. RESULTS: 72 patients were included. Transient quadriceps weakness occurred in 13 patients but resolved by 6 weeks. 30 patients had a significant decrease in MEP amplitude without changes in spontaneous or triggered EMG and SSEP. Two patients had persistent dorsiflexion weakness (3/5 and 1/5) at 2 year follow up. One patient had persistent quadriceps (4-/5) and dorsiflexion (4/5) weakness at 1 year follow up. One patient the surgery was aborted at the time of introduction of retractor due to 69% reduction in MEP and inability to mitigate the changes. All instances of MEP changes were noted during retraction phase. No patient with a negative MEP developed weakness postoperatively. At predetermined level of 50% decrease of amplitude, MEP was 100% sensistive and 65% specific in detecting neural injury. CONCLUSION: MEP monitoring provides additional value to sEMG, tEMG, and SSEP during LLIF at L4-5 to avoid injury. The value of MEP is primarily during maintenance of retraction and not during traversing the psoas muscle where EMG is most valuable.